Non-compliance with outpatient follow-up in child abuse cases - a single centre study/ Siti Rabihah Abdul Halim, Fahisham Taib and Azriani Ab Rahman - Abdul Halim, Siti Rabihah; Taib, Fahisham; Ab Rahman, Azriani (Faculty of Medicine, 2023)
Introduction: To study the characteristics of child abuse cases and determine the risk factors associated with non-compliance to follow-up. Methods: A retrospective review of Suspected Child Abuse and Neglect (SCAN) cases attending an outpatient clinic at Hospital Universiti Sains Malaysia was performed. This was done using a standardized proforma to capture the demographic and clinical data from 2014 until 2020. Variables collected were gender, age at the time of the abuse, religion, education, school attendance, history of previous abuse, parental employment, parental relationship, domestic violence, parental criminal history, substance abuse, and household number. Children under the age of 18 years who were seen by the SCAN team in the emergency department (ED) or during hospital admission within the time frame were included. Results: Compliance rates are defined as the follow-up within the first recommended date given after hospital admission or encounter at the ED. The investigation comprised 311 cases and sexual abuse was reported in 261 cases (83.9%). During the study period, 191 (61.3%) children who were non-compliant with follow-up. Simple binary logistic regression revealed that the significant factors associated with non-compliance to follow-up after the SCAN team review was the patients’ age only. Multiple logistic regression revealed that there were no significant factors associated with failure to comply with outpatient clinic follow-up. Conclusion: This study provides a descriptive study of local child abuse cases. We could not identify any specific factors associated with non-compliance to follow-up.